Instagram Account Management Strategy in Information Dissemination - Anshori, Imam; Yusmanizar, Yusmanizar; Fitriana, Fitriana (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
The National Capital of the Nusantara (IKN) is one of the government policies that influences all aspects of Indonesia. However, moving the capital city from Jakarta to the Nusantara certainly still requires a promotional strategy to spread information about the capital city of the archipelago. This research aims to find out and describe the promotional strategies carried out by the Indonesian capital through the official Instagram @ikn_id. This research uses descriptive qualitative research methods with data collection techniques in the form of interviews, literature studies and documentation. The key informant used in this research is the admin of the official Instagram @ikn_id. The results obtained in this research are that @ikn_id uses several strategies such as timing strategies in uploading posts. Use hashtags to spread the uploads you make, and create informative content to generate interest from the wider community.